PHARMACOKINETIC STUDY OF MATRIX MEMBRANE MODERATED TRANSDERMAL SYSTEM OF BOSENTAN MONOHYDRATE - Mannam, Revathi; Yallamalli, Indira Muzib (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The objective of the present research work is to carry out the pharmacokinetic studies of optimized matrix membrane moderatedtransdermal patch of bosentan monohydrate. Materials and Methods: The matrix membrane moderated transdermal system was formulated using HPMC, HPMC K4M and E RLPO. In vitrodiffusion studies were carried out using modified Franz diffusion cell and for the optimized transdermal patch, pharmacokinetic studies were carriedout using New Zealand male rabbits. Plasma samples were quantified using high-performance liquid chromatography. Results: The in vitro diffusion studies revealed that formulation F3 with HPMC K4M and E RLPO had controlled release up to 28 hrs, and a maximumof 95.02Â±2.68% drug was released. The release kinetics followed mixed order non-Fickian diffusion. The pharmacokinetic studies of the optimizedpatch revealed controlled release up to 45 hrs where a 2.2-fold increase in area under curve (AUC) and 3.8 times increase in mean residence time(MRT) were observed compared to oral route. The results were appeared to be significant at pâ‰¤0.05. The variation in half-life was found to be notstatistically significant when compared between oral and transdermal routes. Conclusion: The pharmacokinetic results concluded that the matrix membrane moderated transdermal system with extended AUC and MRT canenhance the bioavailability of bosentan monohydrate by minimizing the drug-related side effects in oral route.